The Importance of Teaching Islamic Education In Promoting Mental Health (Journal of the College of Basic Education, 2026)
This research examines Islamic Education as an effective educational approach for promoting mental health among primary school students in light of rapid technological transformations and the resulting early and intensive use of technology by children. This situation has led to a range of psychological and behavioral problems, most notably poor concentration, addiction, social isolation, and anxiety associated with continuous interaction with electronic media. The study is based on a central problem concerning how Islamic Education can be employed to support students’ psychological balance, drawing upon its rich ethical values and well-established educational principles that contribute to guiding behavior, regulating emotions, and developing self-awareness.The research aims to identify the dimensions of mental health among primary school students, diagnose the challenges they face in their environment, clarify the Islamic values that can be educationally activated within this context, and measure their impact on improving mental health. The study adopts the descriptive-analytical approach through reviewing and analyzing educational and psychological literature, as well as previous studies, and linking their concepts to the theoretical framework of the research.The theoretical findings indicate that Islamic Education plays a pivotal role in enhancing self-monitoring, behavioral discipline, and time management. It also helps reduce negative emotions and harmful online behaviors while contributing to the development of social intelligence and the establishment of positive relationships with family members, schools, and peers, thereby reducing manifestations of social isolation. The study highlights the importance of integrating modern technology and artificial intelligence into Islamic Education in a conscious and responsible manner that takes into account students’ psychological and physical well-being, thereby achieving a balance between benefiting from modern technologies and protecting mental health. The research recommends strengthening the presence of Islamic educational values in educational programs, training teachers and parents in the field of mental health, and designing safe and interactive educational content. It also calls for future studies to examine the impact of this approach across different age groups, with the aim of building a psychologically and socially balanced generation capable of dealing wisely with the modern world from the earliest stages of education